LEGAL CERTAINTY OF THE MEANING OF STRATEGIC DECISIONS IN LIMITING THE AUTHORITY OF THE REGENT'S EXECUTING DUTIES IN THE FIELD OF PERSONNEL AFFAIRS - Ni Nyoman Inda Yunita Nadia In Putri; Siti Kotijah; Ine Ventyrina; Warkhatun Najidah (Awang Long Law Review, 2026)
This study analyzes the legal certainty of the meaning of strategic decisions in limiting the authority of the acting regent in the field of personnel. The research method used is doctrinal research with a statutory approach and a case approach. The results of the study indicate that legal certainty regarding the meaning of "strategic decisions" has not been adequately realized even though it has been regulated in Article 14 verse (7) of Law Number 30 year 2014 concerning Government Administration and SE BKN Number 1/SE/1/2021, because these regulations are still abstract and multi-interpretable without clear definitions, criteria, and parameters. Strategic decisions in the field of personnel which include the appointment, transfer, and dismissal of employees are the authority of definitive officials, not acting officials who only obtain authority through mandates for routine tasks. This unclear legal meaning creates uncertainty in the practice of regional government administration and has the potential to harm the rights of civil servants.